GOOGLE READING LOGS TO IMPROVE READING ABILITY AND INTEREST - Widyarini, Laksmi (Wiralodra English Journal, 2022)
This study is aimed at 1) determining the procedure for using Google reading logs in improving students' reading skills and interest, and 2) identifying the effect of using Google reading logs on students' reading skills and interest. Participants in this study were early semester students of English Department, Universitas Sarjanawiyata Tamansiswa. The study employed a descriptive qualitative approach. The research data were collected through pre-test/post-test, questionnaires, and interviews. The study was initiated by collecting data regarding relevant facilities in Google Classroom as reading logs. The next phase was collecting data related with the students’ reading interest and skills. The results of the data analysis were then used to determine the procedure for using google reading logs. The data collected from the results of the pre-test/post-test, questionnaires, and interviews were summarized and analyzed. Based on the results of the analysis and data summary, it is concluded that google reading logs improve students' reading ability and interest.